Knowledge of Local Toll-road Pricing in Oslo - Lars Even Egner; Nils Fearnley (Findings)
We investigated knowledge of local toll roads among Oslo residents with a valid driver's license and access to a car through a survey (N = 419; sample: e-scooter users). Knowledge of prices, rules, and rush hour times is limited. Only 0.5-3% of respondents indicate a correct price (±1 NOK) for toll-passings. Correct answers regarding monthly and hourly payment caps are 10% and 17%, respectively. Finally, 4-44% of respondents indicated the correct time when peak hours start or stop.